2000
DOI: 10.3354/meps205123
|View full text |Cite
|
Sign up to set email alerts
|

Zoobenthic community establishment and habitat complexity-the importance of seagrass shoot-density, morphology and physical disturbance for faunal recruitment

Abstract: Seagrass meadows are among the most diverse coastal ecosystems in the Baltic Sea. There is, however, an apparent lack of quantitative data on functional aspects of these systems, such as plant-animal interactions. We tested the importance of seagrass density and morphology for benthic infaunal recruitment in a 2 mo (June/July 1997) field-experiment with both bare and vegetated (3 densities of artificial Ruppia maritima and Zostera marina) colonization trays with azoic sediment. These artificial seagrass patche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(79 citation statements)
references
References 51 publications
5
72
0
2
Order By: Relevance
“…In conclusion, our study is congruent with Bostrom and Bonsdorff (2000), whom stated that structurally complex plant assemblages (like macrophytodetritus) may trap or attract organisms more efficiently than structurally simple leaf canopies or bare sediments. Structural complexity and dispersion drivers, such as hydrodynamics (i.e.…”
Section: Dispersion and Colonization Driverssupporting
confidence: 81%
“…In conclusion, our study is congruent with Bostrom and Bonsdorff (2000), whom stated that structurally complex plant assemblages (like macrophytodetritus) may trap or attract organisms more efficiently than structurally simple leaf canopies or bare sediments. Structural complexity and dispersion drivers, such as hydrodynamics (i.e.…”
Section: Dispersion and Colonization Driverssupporting
confidence: 81%
“…As a function of complex biogeochemical processes (Harris, 1999;Hansen et al, 2000;Eyre and Ferguson, 2002), seagrass meadows are extremely productive systems, which exhibit high biodiversity, and support complex food webs, constituting a habitat refuge for a number of organisms (Orth, 1992;Boström and Bonsdorff, 2000;Borum et al, 2005). Changes in seagrass areas are often a symptom of major changes in environmental characteristics, and therefore constitute an important indicator for assessing the state of the environment.…”
Section: Angiospermsmentioning
confidence: 99%
“…Coralline algae had a higher rate of sediment retention by a stem, which benefits the associated invertebrate fauna by decreasing the negative effects of the physical stress of desiccation, reducing the mortality rate due to predation, increasing available space for the establishment of new larvae, refuge for many invertebrates that inhabit their fronds and also use them as food (BOSTRÖM & BONSDORFF 2000, KELAHER 2002. In the present study all chitons species, both adults and juveniles, which were found on the three phytals demonstrated a preference for the winter periods, between May and September.…”
Section: Discussionmentioning
confidence: 99%